If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(x) = log(x + -1) Multiply g * x gx = log(x + -1) Reorder the terms: gx = glo(-1 + x) gx = (-1 * glo + x * glo) gx = (-1glo + glox) Solving gx = -1glo + glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'glo' to each side of the equation. glo + gx = -1glo + glo + glox Combine like terms: -1glo + glo = 0 glo + gx = 0 + glox glo + gx = glox Add '-1glox' to each side of the equation. glo + -1glox + gx = glox + -1glox Combine like terms: glox + -1glox = 0 glo + -1glox + gx = 0 Factor out the Greatest Common Factor (GCF), 'g'. g(lo + -1lox + x) = 0Subproblem 1
Set the factor 'g' equal to zero and attempt to solve: Simplifying g = 0 Solving g = 0 Move all terms containing g to the left, all other terms to the right. Simplifying g = 0Subproblem 2
Set the factor '(lo + -1lox + x)' equal to zero and attempt to solve: Simplifying lo + -1lox + x = 0 Solving lo + -1lox + x = 0 Move all terms containing g to the left, all other terms to the right. Add '-1lo' to each side of the equation. lo + -1lox + -1lo + x = 0 + -1lo Reorder the terms: lo + -1lo + -1lox + x = 0 + -1lo Combine like terms: lo + -1lo = 0 0 + -1lox + x = 0 + -1lo -1lox + x = 0 + -1lo Remove the zero: -1lox + x = -1lo Add 'lox' to each side of the equation. -1lox + lox + x = -1lo + lox Combine like terms: -1lox + lox = 0 0 + x = -1lo + lox x = -1lo + lox Add '-1x' to each side of the equation. x + -1x = -1lo + lox + -1x Combine like terms: x + -1x = 0 0 = -1lo + lox + -1x Simplifying 0 = -1lo + lox + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
g = {0}
| (28b-4)-9(3b+4)=-6 | | x+90+66=180 | | x+90+41+27=180 | | (28b-4)-9(3b+4)=6 | | x+29+90=180 | | 19=y-10 | | x+61+90=180 | | x=61 | | x+90+29=180 | | 6y^2+13y-5= | | 7x^2+6x+3= | | X-0.3=9.3 | | x+162=180 | | 30000.00x=-275000.00+45000.00x | | 30000.00x=350000.00 | | 30000.00x=350.000 | | 1=y-9 | | 8x^2=36 | | 5z-(13-2y)=59 | | -275000.00+45000.00x=0 | | -6w+8=6w+5 | | X-0.8=7.6 | | 40-n=3n-16 | | 6x+8.88=4x+12 | | (f+g)(x)-6x-1andg(x)=4x^2 | | -9-1=-6+x | | n+14+6n-52=32 | | 10-(8-Q)=20-2*Q | | -8x+7+9x=-23+21 | | -3-12=5x+16-4x | | 7x+17-6x=-4-11 | | 4n-20-7n+16-3=35 |